Reduction in Cutis Verticis Gyrata after Transsphenoidal Pituitary Resection of Growth Hormone–Secreting Adenoma - Pinggera, Daniel; Marsoner, Delia Anna; Seiz-Rosenhagen, Marcel; Thomé, Claudius; Franz Freyschlag, Christian (Indian Journal of Neurosurgery, 2016)
Aim Cutis verticis gyrata (CVG) describes a hypertrophy and folding of the skin that appears as gyration of the scalp. Secondary CVG is a common symptom of growth hormone (GH)–producing adenoma of the pituitary and an early sign of acromegaly. We hypothesized that surgical removal of a pituitary adenoma with a consecutive decrease in hormone levels will cause a reduction in gyration.Methods Imaging and laboratory examination of 10 patients (median age: 44 years) with GH-producing adenoma have been evaluated retrospectively. Surgical treatment consisted of endonasal transsphenoidal resection of the adenoma, followed by endocrinologic and radiographic follow-up. CVG was calculated as area under the curve of the scalp on preoperative coronal T1-weighted MRI, compared with postoperative follow-up imaging after 12 months (AUC, measured in cm2). In laboratory examination, the levels of insulin-like growth factor-1 (IGF-1) were analyzed accordingly as its levels are constant throughout the day.Results After 12 months, we found a statistically significant (p = 0.008) correlation between the decrease in IGF-1 levels (median: 219.00 ng/mL) and the reduction in CVG (median: 0.12 cm2).Conclusion Resection of GH-producing pituitary adenoma leads to a decrease in CVG in patients suffering from acromegaly, which is strongly related to the levels of IGF-1
Keywords: acromegaly; cutis verticis gyrate; pituitary adenoma